Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.13031/trans.13989
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Leaf Water Content with a Portable NIRS System Based on Deep Learning and Information Fusion Analysis

Abstract: HighlightsA portable NIRS system with local computing hardware was developed for leaf water content determination.The proposed convolutional neural network for regression showed a satisfactory performance.Decision fusion of multiple regression models achieved a higher precision than single models.All of the devices and machine intelligence algorithms were integrated into the system.Software was developed for system control and user interface.Abstract. Spectroscopy has been widely used as a valid non-destructiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This results in researchers exploring new methods to improve NIR in this application. Other application 'hot spots' include grain, 28,37,[48][49][50][51][52] organic matter such as leaves, wood and beans, [53][54][55][56][57][58][59] food powders, 37,60,61 oil 62 and brain, 63 with 7, 7, 3, one and one papers, respectively.…”
Section: Cnn For Nir Spectroscopymentioning
confidence: 99%
“…This results in researchers exploring new methods to improve NIR in this application. Other application 'hot spots' include grain, 28,37,[48][49][50][51][52] organic matter such as leaves, wood and beans, [53][54][55][56][57][58][59] food powders, 37,60,61 oil 62 and brain, 63 with 7, 7, 3, one and one papers, respectively.…”
Section: Cnn For Nir Spectroscopymentioning
confidence: 99%
“…Many studies have reported that abundant, diverse, and well-proportioned samples can significantly improve the efficiency of models in spectroscopic analysis, both qualitatively and quantitatively [1][2]. Moreover, with the emergence of the big data era, deep learning (DL) algorithms have been widely applied to spectral analysis, posing a greater challenge to the number of spectral samples due to the data sensitivity of these algorithms [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…As a subclass of machine learning methods, deep learning (DL) models have recently realized 'success in the field of plant nutrient status diagnosis, which refers to using deep neural networks that include a pretty large number of processing layers to analyze and process data. Since the early 2000s, DCNNs have been utilized for analyzing RGB images [25], such as images segmentation of biological materials [26], recognition of plants [27], prediction of leaf water content [28] and plant diseases detection [29]. Additionally, DCNNs automatically learn and extract the most descriptive features from the images during the training process, which thoroughly addresses the problems of hand-crafted features [30].…”
Section: Introductionmentioning
confidence: 99%